Microfabrication strageties for annulus fibrosus tissue engineering - Chuah, Yon Jin (2015)
Lower back pain associated with disc degenerative diseases is a major musculoskeletal health concern worldwide. Spinal fusion has some efficacy pain management for serious disc degenerative diseases but often underscores the importance of biological approaches in intervertebral disc regeneration. Development of a biological disc construct for the past decades is still inferior to the native disc especially in annulus fibrosus (AF) tissue engineering, thus limiting its translational application. Furthermore, the limited access to obtain healthy autologous AF cells required bioengineers to source for alternative cells such as mesenchymal stem cells (MSCs). Two different microfabrication procedures were established to create a simple engineered AF tissue model for the investigation in MSCs-based AF tissue engineering, and a novel engineered AF construct with micro-architecture, biochemical composition, functionality and mechanical strength similar to the native tissue which is expected to be an important prototype towards the therapeutic treatments of degenerative disc disease.